2007
DOI: 10.1111/j.1469-8129.2007.00268.x
|View full text |Cite
|
Sign up to set email alerts
|

Who ate all the pride? Patriotic sentiment and English national football support

Abstract: The growing popularity of English national insignia in international football tournaments has been widely interpreted as evidence of the emergence of a renewed English national consciousness. However, little empirical research has considered how people in England actually understand football support in relation to national identity. Interview data collected around the time of the Euro 2000 and the 2002 World Cup tournaments fail to substantiate the presumption that support for the England football team maps on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(51 citation statements)
references
References 25 publications
2
49
0
Order By: Relevance
“…This evidence adds some weight to that provided by Abell et al who suggested that support for the national team is not necessarily strongly associated with feelings of English national sentiment. [38] …”
Section: Feeling Represented By the England Team And Nationalitymentioning
confidence: 99%
See 1 more Smart Citation
“…This evidence adds some weight to that provided by Abell et al who suggested that support for the national team is not necessarily strongly associated with feelings of English national sentiment. [38] …”
Section: Feeling Represented By the England Team And Nationalitymentioning
confidence: 99%
“…[16] Contrasting evidence from Abell, Condor, Lowe, Gibson and Stevenson suggests that English football fans' articulations of support for the national team do not even necessarily represent their wider feelings of national sentiment. [17] Although Abell et al interviewed a broad sample of English individuals, only some of them were actually football fans. Therefore, the aim of the current study was to provide firmer evidence from fans themselves.…”
Section: Introductionmentioning
confidence: 99%
“…(Elias, 1991: 202) Nationalism and soccer in the global age Carrington (1999) reminds us that support for the England soccer team has been used as a vehicle for the promotion of overtly nationalist and racist political projects such as the farright British National Party. At the same time -and perhaps for these reasons -many England fans have disassociated themselves from such overtly political perspectives by downplaying any nationalist element to their soccer support (Abell et al, 2007). Either way, the connection between English nationalism and soccer fandom is more problematic than has generally been recognised.…”
Section: English Nationalism and Sportmentioning
confidence: 93%
“…‗Everyday' forms of fandom are also an area largely ignored in previous research, in favour of the ‗exceptional' sports fan (Crawford, 2004), notably the hooligan (Giulianotti, 1999;King, 2002). This has been particularly problematic in studies of nationalism, appearing to offer inflated accounts of nationalist sentiment among England soccer fans (see Abell, Condor, Lowe, Gibson, & Stevenson, 2007). We therefore outline a methodological approach that takes account of the ‗everyday' consumption of soccer in England, using pubbased participant observation and an online survey posted within web based soccer discussion forums.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Abell et al suggest that English football fans" articulations of support for the national team do not even necessarily represent their wider feelings of national sentiment. [10] More empirical evidence is required to help determine the meaning of football fandom practices to the articulation of English identity.…”
Section: Football Fandom As An Articulation Of English National Identmentioning
confidence: 99%